Our Environmental Value Orientations Influence How We Respond to Climate Change - Marshall, N. A.; Thiault, L.; Beeden, A.; Beeden, R.; Benham, C.; Curnock, M. I.; Diedrich, A.; Gurney, G. G.; Jones, L.; Marshall, P. A.; Nakamura, N.; Pert, P. (Frontiers in Psychology, 2019)
People variably respond to global change in their beliefs, behaviours, and grief (associated with losses incurred). People that are less likely to believe in climate change, adopt pro-environmental behaviours, or report ecological grief are assumed to have different psycho-cultural orientations, and do not perceive changes in environmental condition or any impact upon themselves. We test these assumptions within the context of the Great Barrier Reef (GBR), a region currently experiencing significant climate change impacts in the form of coral reef bleaching and increasingly severe cyclones. We develop knowledge of environmental cultural services with the Environmental Schwartz Value Survey (ESVS) into four human value orientations that can explain individuals' environmental beliefs and behaviours: biospheric (i.e., concern for environment), altruistic (i.e., concern for others, and intrinsic values), egoistic (i.e., concern for personal resources) and hedonic values (i.e., concern for pleasure, comfort, aesthetic, and spirituality). Using face-to-face quantitative survey techniques, where 1,934 residents were asked to agree or disagree with a range of statements on a scale of 1-10, we investigate people’s (i) environmental values and value orientations, (ii) perceptions of environmental condition, and (iii) perceptions of impact on self. We show how they relate to the following climate change responses; (i) beliefs at a global and local scale, (ii) participation in pro-environmental behaviours, and (iii) levels of grief associated with ecological change, as measured by respective single survey questions. Results suggest that biospheric and altruistic values influenced all climate change responses. Egoistic values were only influential on grief responses. Perception of environmental change was important in influencing beliefs and grief, and perceptions of impact on self were only important in influencing beliefs. These results suggest that environmental managers could use people’s environmental value orientations to more effectively influence climate change responses towards environmental stewardship and sustainability. Communications that target or encourage altruism (through understanding and empathy), biospherism (through information on climate change impacts on the environment), and egoism (through emphasizing the benefits, health and wellbeing derived from a natural resource in good condition), could work.